2001
DOI: 10.1590/s1516-35982001000200029
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de vacas Charolês e Nelore desterneiradas aos três ou sete meses

Abstract: RESUMO -Foi avaliado o desempenho de vacas Charolês (C) e Nelore (N), agrupadas em três classes de idade, jovens (3 e 4 anos), adultas (5 a 7 anos) e velhas (8 ou mais anos), desmamadas aos três (precoce) ou sete meses no outono (tradicional). O peso no outono das vacas desterneiradas aos três meses (T3) foi 45 kg superior ao das vacas com remoção do bezerro aos sete meses (T7). O estado corporal aos sete meses também foi melhor nas vacas do T3 (3,3 contra 2,1 pontos). Vacas do T3 apresentaram maior ganho de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
13

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 2 publications
0
12
0
13
Order By: Relevance
“…The weaning weight of the calves behaved according to their performance from birth to weaning, and the latter was correlated with milk yield 0.6161 (P<0.0003), demonstrating the importance of this trait in the production of breeding herds. Restle et al (2001) emphasized the importance of milk yield, stating that it cannot be an inhibitory factor for the subsequent reproduction, and that the nutritional management of the herd should consider requirements of beef cows in the different physiological stages (MONTIEL; AJUHA, 2005); these factors are potentiated in extensive systems held on natural pastures, due to nutritional restrictions (VAZ; LOBATO, 2010b). However, Pimentel et al (2005) found, in Hereford cows reared in extensive conditions, that milk yield was not a limiting factor to post-calving fertility.…”
Section: Resultsmentioning
confidence: 99%
“…The weaning weight of the calves behaved according to their performance from birth to weaning, and the latter was correlated with milk yield 0.6161 (P<0.0003), demonstrating the importance of this trait in the production of breeding herds. Restle et al (2001) emphasized the importance of milk yield, stating that it cannot be an inhibitory factor for the subsequent reproduction, and that the nutritional management of the herd should consider requirements of beef cows in the different physiological stages (MONTIEL; AJUHA, 2005); these factors are potentiated in extensive systems held on natural pastures, due to nutritional restrictions (VAZ; LOBATO, 2010b). However, Pimentel et al (2005) found, in Hereford cows reared in extensive conditions, that milk yield was not a limiting factor to post-calving fertility.…”
Section: Resultsmentioning
confidence: 99%
“…As vacas submetidas a DP tiveram PFA significativamente (P<0,05) superiores àquelas submetidas Tabela 2 -Peso vivo (PIA) e condição corporal ao início do acasalamento (CIA), conforme os tratamentos e a raça das vacas (Moraes & Lobato, 1993;Simeone & Lobato, 1996;Lobato et al, 1999;Restle et al, 2001;Lobato et al, 2000;Fagundes et al, 2003;Marques et al, 2000), indicando mudança na partição dos nutrientes, quando retirada a amamentação, diminuindo as exigências nutricionais das vacas e permitindo às mesmas recuperarem CC.…”
Section: Resultsunclassified
“…Segundo Short et al (1994), a presença do bezerro ao pé da vaca e o ato de mamar criam uma série de estímulos metabólicos, nervosos e fisiológicos, os quais podem impedir a vaca de retomar o seu ciclo estral. A utilização do desmame dos bezerros a idades precoces (60-110 dias) é eficiente em incrementar a fertilidade das vacas (Simeone & Lobato, 1996;Lobato et al, 1999;Marques et al, 2000;Restle et al, 2001;Fagundes, 2001).…”
Section: Pötter and Lobatounclassified
“…Entre as vantagens do desmame precoce frente ao desmame convencional realizado aos 7 meses de idade dos animais, destacam-se o incremento nos índices de prenhes (Pascoal & Vaz, 1997;Restle et al, 2001) e a melhoria do estado corporal para os partos subseqüentes (Makarechian et al, 1988). Trabalhos de pesquisa realizados por Barcellos et al (1995) e Sá et al (1997) também demonstraram que o desmame precoce de bezerros condiciona a maior ganho de peso das vacas no pós-desmame, melhorando os índices reprodutivos subseqüentes.…”
Section: R Bras Zootec V31 N4 P1803-1813 2002unclassified